Peningkatan Hasil Belajar Siswa Kelas V dengan Penerapan Model Pembelajaran Kooperatif Tipe STAD - Syafitri Syafitri (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The main problem of this research is the starting point of the low learning outcomes of grade V SDN 1 Sijunjung caused by the conventional learning process. Learning that is passive and does not create student creativity results in learning goals that are not optimal. The purpose of this study was to determine the improvement of student learning outcomes in grade V SDN 1 Sijunjung by applying the STAD learning model. The method used is Classroom Action Research (PTK) which consists of two cycles, with each cycle consisting of 2 meetings. Each hypothesis cycle was tested through hasial learning data from 20 grade V students of SDN 1 Sijunjung 2019/2020 academic year through observation and documentation techniques. The data analysis technique used is qualitative and quantitative analysis. The results showed that the pre-test data for the cognitive aspects were 1375 with a mean of 68,75, then after the application of the STAD learning model, the number of values increased by 21,75 points to 1810 with a mean of 90,50. Meanwhile, the pre-test data for the psychomotor aspect amounted to 1415 with a mean of 70,75 and the post-test increased by 9,75 points to 1690 with a mean of 84,50. Thus the application of the STAD learning model can improve the learning outcomes of fifth grade students at SDN 1 Sijunjung.